(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT The eclipse and the lunar eclipse signify the greatness of God Almighty in the events of this universe, So God sent His messengers to warn people and fulfill their religion and meet their inevitable day. He sent with them clear verses to be evidence of His existence, glory and majesty, and His authority, and to scare them with His torment. We send messengers except as evangelizers and evangelists, so whoever believes and is righteous, there is no fear for them, nor do they grieve . These sun verses and the moon, the Almighty said: omn verses the night and day and the sun and the moon will not bow down to the sun nor the moon, and worship to God who created them, if ye him Tabdon . This will be throughout the research (eclipse prayer and eclipse), The importance of these two verses in human life and their the righteous deeds. Encouraqed me to to write this research about them and about the issues mentioned in hadiths in hadith books.